Relationship between serum sodium, serum potassium levels and ankle reflex grades in malnourished children - Ukil, Protiksha; S., Srikanth; T., Usha Rani; K., Siva Ram Prasad (International Journal of Contemporary Pediatrics, 2022)
Background: Malnutrition among children is a major health issue in South East Asia presenting with stunting and wasting. Many research studies have been conducted to establish the signs, symptoms, corresponding effects of malnutrition on child health, growth and development and the current study focusses more specifically on the effects of electrolyte levels on ankle reflex grades in malnourished children. Methods: This is an observational case-control type of study conducted in two teaching hospitals in India. Cases of protein-energy malnutrition (PEM) (n=30), children with mid upper arm circumference (MUAC) lesser than 12.5 along with control group of normal healthy children (n=30), all aged between 1 and 5 years were selected. Ankle reflexes were noted using a knee hammer on three consecutive days and graded based on the NINDS reflex grading scale for cases and controls and noted against the corresponding serum sodium and serum potassium values obtained from the children. Results: A Chi square test performed and p=0.379 obtained for serum sodium and 0.026 for serum potassium for cases. Conclusions: A conclusion could be drawn that serum sodium levels and ankle reflex grades have no statistically significant relationship in cases of controls, while serum potassium levels and ankle reflex grades have statistically significant relationship in cases but not in control group indicating a plausible cause for hyporeflexia in the patients.